Prolonged Fever and Unremitting Back Pain in Elderly Patient: A Case of Disseminated Tuberculosis with Spondylodiscitis - Mohd Abdul Ghani, Nashithatul Amani; Mohamad, Noraini; Abdul Kadir, Azidah; Samri, Shafora Bibi; Salim, Azizul Akram; Abdullah, Nurul Huda (IIUM Medical Journal Malaysia, 2026)
Disseminated tuberculosis (DTB) is a life-threatening condition caused by the hematogenous spread of Mycobacterium tuberculosis. As the clinical presentation is often nonspecific, it leads to late diagnosis. We reported a case of a 75-year-old man who presented with intermittent fever for one month and lower back pain for four months. Bronchoscopy with bronchoalveolar lavage revealed low-level of Mycobacterium tuberculosis, leading to a diagnosis of smear-negative pulmonary tuberculosis. Magnetic resonance imaging of the thoracolumbar spine showed multiple enhancing skip lesions involving thoracic and lumbar vertebrae bodies with a T8/T9 paravertebral abscess compressing onto the spinal cord, suggestive of tuberculous spondylodiscitis and confirming a diagnosis of DTB. The patient’s condition improved with anti-tuberculosis therapy. This case emphasizes the need for high clinical suspicion in patients with multisystem involvement and the importance of timely, targeted investigations to confirm the diagnosis.